A Retrospective Look at How Well a Macro‐Micro Model Can Analyze the Impact of the Global Financial Crisis on a Developing Country. Issue 3 (September 2015) - Chitiga, Margaret; Decaluwe, Bernard; Mabugu, Ramos; Maisonnave, Helene; Robichaud, Veronique; Shepherd, Debra; Van Der Berg, Servaas; Von Fintel, Dieter
<x xml:space="preserve">Abstract</x> This article is a follow‐up to one that looked at the impact of the economic crisis on child poverty in South Africa using a macro–micro modeling technique. The current article's contribution is to position the results of the first article in the context of the actual effects of the crisis. Hence, this article offers a comparative analysis between the results of the modeling with the actual observed outcomes. It also offers explanations for why some model results are different from what obtained in the country after the crisis period.